Analisis Pengawet Natrium Benzoat pada Selai Stroberi Curah di Pasar Tradisional - Chintya Putri Wira Dhika Luwitono; Petrus Darmawan (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Sodium benzoate is an artificial preservative that works to make food last longer. The maximum limit of the use of sodium benzoate on fruit jam according to SNI 01-0222-1995 is 1 g/kg. Strawberry jam in the market is possible to use preservative sodium benzoate that exceeds the quality standard so an analysis is needed. Determination of preservative levels of sodium benzoate in strawberry jam according to SNI 01-2894-1992 using the alkalimetry method. The principle of this method is the neutralization reaction between acids and bases, where H+ ions from acids will react with OH- ions from bases to form a neutral salt. The filtrate resulting from the extraction of the strawberry sample is evaporated on a water bath and the residue obtained is dried in a desiccator. The residue was dissolved in neutral 70% ethanol and added with a 1% PP indicator solution. The solution is then titrated with a standard NaOH solution. The end point of the titration is marked with a constant pink color. Based on the results of the study, there were 10 samples of bulk strawberry jam sold in several traditional markets in Jebres sub-district, Surakarta, where 8 samples were positively containing sodium benzoate. The preservative concentration of sodium benzoate in the A1 market sample is 1.327 g/kg, market sample A2 is 1.490 g/kg, market sample B1 is 1.030 g/kg, market sample B2 is 1.451 g/kg, market sample C2 is 1.444 g/kg, E market sample is 1.077 g/kg, F1 market sample is 1.431 g/kg and F2 market sample is 1.635 g/kg. When compared with the maximum limit of the use of sodium benzoate, bulk strawberry jam sold in several traditional markets in Jebres sub-district Surakarta which is positive sodium benzoate does not meet the requirements of SNI 01-0222-1995.